Phytochemical Screening and Biological Activities of Combretum adenogonium Leaves Extracts - Martial S. Nounagon; Durand Dah-Nouvlessounon; Christine N’tcha; Sani M. Akorede; Haziz Sina; Pacôme A. Noumavo; Farid Baba-Moussa; Farid Bade; Adolphe Adjadohoun; Lamine Baba-Moussa (European Scientific Journal, ESJ, 2017)
Combretum adenogonium is beniniens pharmacopoeia medicinal plant used for the treatment of various diseases. This work aims to study the phytochemical and assess some biological activities of C. adenogonium leaves extracts. The phytochemical analysis (qualitative et quantitative) was conducted by standard analytical chemistry method. Antioxydant activity was evaluated by the DPPH method. Antibacterial activity was evaluated in vitro with 10 references strains , 10 Staphylococcus strains isolated from European Scientific Journal October 2017 edition Vol.13, No.30 ISSN: 1857 – 7881 (Print) e - ISSN 1857- 7431 359 meat products and 10 clinical Staphylococcus aureus strains isolated from Buruli ulcer lesions and pus. The Minimum Inhibitory Concentration (MIC) and Bactericidal (CMB) were determined by macrodilution method. The extracts cytotoxic effect was evaluated with Artemia salina larvae. The phytochemical screening revealed the presence of flavonoids, tannins, anthocyanins, saponin and triterpenoids. The methanolique extract present the higest content (450.66 ± 0.004 µg EAG/mg) of total polyphenolic compound. The results showed the good antioxidant activity. The inhibitory diameter zone vary (p < 0.001) according to the strains. The largest medium inhibitory diameter (21.85 ± 0.17 mm) was obtained with the ethanolic extract, while the lowest (6.00 ±0.00 mm) were recorded with water-ethanol extract. The variation between CMI and CMB is not significant (p > 0.05). The higher LD50 (27.66 mg/ml) was recorded with methanol extract. The results of this study confirm some use of C. Adenogonium extracts. But; these extracts must be use with moderation